2011
DOI: 10.1007/s10896-011-9374-4
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Link Between Domestic Violence Victimization and Loneliness in a Dutch Community Sample: A Comparison Between Victims and Nonvictims by Type D Personality

Abstract: The current study investigated whether differences in loneliness scores between individuals with a distressed personality type (type D personality) and subjects without such a personality varied by domestic violence victimization. Participants (N = 625) were recruited by random sampling from the Municipal Basic Administration of the Dutch city of ‘s-Hertogenbosch and were invited to fill out a set of questionnaires on health status. For this study, only ratings for domestic violence victimization, type D perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
0
5
0
1
Order By: Relevance
“…These personality changes may be a chronic condition and may have as the consequence occurrence of complex post-traumatic stress disorder or other mental disorders. Also, there are several studies that point to important role of personality traits in the occurrence of mental health problems in victims of domestic violence, as well as the interaction between a certain type of personality and domestic violence victimization ( 25 ). The research results of Motevaliyana et al ( 26 ) conducted among women in Iran indicate the importance of personality traits in the understanding of domestic violence, making of strategies for prevention of domestic violence as well as treatment plan.…”
Section: Discussionmentioning
confidence: 99%
“…These personality changes may be a chronic condition and may have as the consequence occurrence of complex post-traumatic stress disorder or other mental disorders. Also, there are several studies that point to important role of personality traits in the occurrence of mental health problems in victims of domestic violence, as well as the interaction between a certain type of personality and domestic violence victimization ( 25 ). The research results of Motevaliyana et al ( 26 ) conducted among women in Iran indicate the importance of personality traits in the understanding of domestic violence, making of strategies for prevention of domestic violence as well as treatment plan.…”
Section: Discussionmentioning
confidence: 99%
“…Bonomi et al, 2007;Cerulli et al, 2012), and loneliness (e.g. Eisikovits & Band-Winterstein, 2015;Kunst & van Bon-Martens, 2011). In addition to these mental health outcomes, it was found that IPV victimisation also negatively affected relationship satisfaction (e.g.…”
Section: Victimisation Experiencesmentioning
confidence: 99%
“…It has been shown that loneliness is associated with the metabolic syndrome in middle aged and older adults (Whisman, 2010), and that loneliness may increase biological aging (Hawkley & Cacioppo, 2010). Although not much is known on the direct link of loneliness and diabetes, loneliness is an issue for people with Type D personality (Beutel et al, 2017;De Moor, Denollet, & Laceulle, 2018;Kunst & Van Bon-Martens, 2011).…”
Section: Introductionmentioning
confidence: 99%